2023
DOI: 10.1371/journal.pone.0283367
|View full text |Cite
|
Sign up to set email alerts
|

Extrauterine growth restriction in very low birth weight infants according to different growth charts: A retrospective 10 years observational study

Abstract: Background Extrauterine growth restriction (EUGR) is common among very low birth weight (VLBW) infants and associated with poor neurodevelopmental outcomes. There are two types of EUGR definitions (cross-sectional and longitudinal) and many growth charts for monitoring postnatal growth. Aims of our study were 1) to compare the rate of small for gestational rate (SGA) and EUGR in a population of VLBW infants, both according to different growth charts (Fenton, INeS charts and Intergrowth-21) and different defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Our study revealed that extremely and very preterm neonates had a higher prevalence of EUGR at discharge concerning weight, according to Fenton2013 charts compared to INTERGROWTH-21st charts. This is in accordance with other studies [46][47][48], and particularly, a recent study by Starc et al reported a decreased prevalence of EUGR of weight when INTERGROWTH-21st charts were used in comparison to Fenton. The differences in outcomes between these two growth charts were expected and can be attributed to the fundamental disparities in the way they were created.…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed that extremely and very preterm neonates had a higher prevalence of EUGR at discharge concerning weight, according to Fenton2013 charts compared to INTERGROWTH-21st charts. This is in accordance with other studies [46][47][48], and particularly, a recent study by Starc et al reported a decreased prevalence of EUGR of weight when INTERGROWTH-21st charts were used in comparison to Fenton. The differences in outcomes between these two growth charts were expected and can be attributed to the fundamental disparities in the way they were created.…”
Section: Discussionsupporting
confidence: 93%
“…This study explored the incidence and risk factors for EUGR in VLBW infants at a single center. The incidence of EUGR varies from 21.7% to 77.2% depending on the definitions employed [1][2][3][4][5][6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…Extrauterine growth restriction (EUGR) is prevalent in preterm and very low birth weight (VLBW) infants. The incidence of EUGR varies from 21.7% to 77.2% depending on the definitions employed [1][2][3][4][5][6][7][8][9] . EUGR is generally defined as an anthropometric measure (mainly weight) below a cut-off value, often the 10th percentile, based on the postmenstrual age (PMA) of the preterm infant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations